Stimulating milk production in milk-deficit countries of Africa and Asia - Brumby, P.J.; Gryseels, Guido (1984)
Discusses issues in the development of dairying in Africa & Asia, outlining main approaches employed in the organization of production, and the need to take into consideration five interrelated factors in dairy development strategies, viz, the supply of dairy stock, animal health, fodder systems, marketing arrangements and training of farmers; also points out the need for research, and institutional support in the form of advisory & extension services as well as credit provision to assist in dairy development.